The Effect of Teachers’ Pedagogical Competence on Improving Learning Motivation of Fourth Grade Students at SD Gugus Pattimura, Comal District, Pemalang Regency - Aprilianto, Kukuh Andy; Apriani, Dewi; Munadi, Munadi (MASI Mandiri Edukasi, 2026)
This article aims to conceptually examine the role of teachers’ pedagogical competence in enhancing students’ learning motivation within the primary education context, linking it to current educational policies and classroom practices. The study employs a literature review approach, complemented by preliminary empirical data from limited observations and interviews at the research site, as outlined in the thesis proposal. Data were analyzed descriptively and analytically, dialoguing conceptual insights with initial empirical findings, relevant learning motivation theories, pedagogical competence frameworks, and prior studies. The findings indicate that teachers’ pedagogical competence—particularly in understanding student characteristics, designing instructional activities, and utilizing interactive learning media—plays a crucial role in fostering students’ learning motivation. These results emphasize the need to enhance teachers’ pedagogical skills to improve instructional quality continuously. The novelty of this article lies in synthesizing the conceptual link between teachers’ pedagogical competence and students’ learning motivation, contextualized within actual classroom practices, providing a strong basis for future quantitative research.